The impact of the Basel Accords in lending activity: The case of Portugal and Germany - Sabino, Ana Rita Teixeira Borges (2017)
The impact of the Basel Accords implementation in lending availability is approached in this dissertation. Based in Naceur and Kandil (2013) models, the Portuguese and the German banking sectors are assessed, having in mind the main question: did the Basel Accords implementation reduced lending availability? Our findings show that lending was reduced after implementation of the Basel Accords but also due to macroeconomic conditions. However, some limitations in this study are found in the end of the analysis.